A produção do conhecimento sobre capoeira na Universidade Federal do Tocantins - Silva, Lindomar Gomes da (Universidade Federal do Tocantins, 2021)
The present work had as objective to verify the production of scientific knowledge of professors and students of the Federal University of Tocantins (UFT), having as main subject the Capoeira, identifying in which areas, courses and campuses the works were produced, theare a of formation and performance of the advisors, which is discussed on the topic with in the UFT. In this study, a bibliometric survey of all the scientific works produced was carried out and, what fits within the propos al out lined here, were identified and divided by campus, for a better elucidation of what has been written about Capoeira at the Federal University of Tocantins. In this sense, we point out that the campus /Pedagogy course in Arraias-Tohasstood out in the production of works on capoeira in TCC.